تحديد الرصاص والكادميوم في لحوم وأكباد وكلى الخراف المعروضة في الأسواق المحلية لمدينة اللاذقية - الحكيم قصي (Latakia University Journal -Biological Sciences Series, 2016)
هدفت هذه الدراسة إلى تحديد مستويات الرصاص والكادميوم في لحوم وكلى وأكباد الخراف المعروضة في الأسواق المحلية لمدينة اللاذقية, ومقارنة النتائج مع ما هو منشور في البلاد الأخرى, ومع الحدود القصوى المسموح بها للاستهلاك البشري, وقد تم التحليل باستخدام مطياف الامتصاص الذري ( AAS ). بلغ متوسط تركيز الرصاص في اللحم والكلى وأكباد الأغنام 0.043 , 0.284 , 0.118 ملغ/كلغ من الوزن الرطب, على التوالي, وبلغ متوسط تركيز الكادميوم 0.017 , 0.173 , 0.252 ملغ/كلغ من الوزن الرطب, على التوالي, وقد بين التحليل الإحصائي وجود فروق معنوية في تركيز الرصاص والكادميوم بين كل من الأكباد والكلى واللحم (P<0.05) وكان متوسط تركيز الرصاص والكادميومِ في عيناتِ النسج المختلفة أقل عموماً مِنْ الحدود القصوى المسموح بها لدى المفوضية الأوربية (EC). أوضحت نتائج هذه الدراسة أن الأكباد هي أكثر الأنسجة المدروسة تركيزا للرصاص يليه الكلى ثم اللحم , بينما كان تراكم الكادميومِ أعلى في الكِلى يليه الأكباد ثمّ اللحم, وقد بدا ذلك جليا لكل من الرصاص والكادميوم عند أمهات الأغنام التي يحتفظ بها لأعمار كبيرة نسبيا. The aim of the present study was to determine the levels of lead and cadmium in the meat, liver and kidney of sheep exposed in the local markets of the city of Latakia, and to compare the results with those reported by other countries and with the maximum acceptable levels for human consumption, Lead and cadmium were determined by atomic absorption spectrometry (AAS). The mean concentrations of lead in meat, liver and kidney were 0.043, 0.284 and 0.118 mg/kg fresh weights, respectively, while mean concentrations of cadmium were 0.017, 0.173 and 0.252 mg/kg fresh weights, respectively. Statistical analysis showed a significant difference in lead and cadmium concentrations between liver and kidney and in meat (P<0.05). The mean concentration of lead and cadmium in tissue samples was generally lower than the maximum acceptable concentration in the European Commission (EC). The results showed high levels of lead accumulation in the liver followed by kidneys then meat, While cadmium accumulation was highest in the kidneys followed by liver then meat, associated it was clear that accumulation of both lead and cadmium was high in female sheep and could be due to the be due to the higher age of female animals.